Analysis of Village Government Service Quality in Efforts to Improve Community Satisfaction - Aprilia Sri Mulyaningsih; Wisudani Rahmaningtyas (Economic Education Analysis Journal, 2025)
This study is motivated by the unsatisfactory quality of public services provided by the village government, which is perceived as lacking in promptness and responsiveness. Additionally, there is limited availability of information regarding the requirements and procedures for managing population-related documents. This research adopts a descriptive qualitative approach. The focus of the study is the quality of public services in Tutup Village, Tunjungan Sub-district, Blora Regency, particularly in efforts to improve community satisfaction. Data were collected through interviews, documentation, and observation. To assess service quality, five dimensions were employed: (1) Tangible, referring to the condition of infrastructure and room comfort; (2) Reliability, related to staff competence and service appropriateness; (3) Responsiveness, covering service duration and operating hours; (4) Empathy, which includes the provision of solutions and the level of public education and outreach; and (5) Assurance, referring to staff friendliness and service costs. The findings indicate that the quality of services provided by the government of Tutup Village has been implemented adequately. However, improvements in supporting facilities and infrastructure are still needed to optimize the outcomes of the services delivered to the community.